Molecular screening of local Indonesian rice to identified resistant varieties against brown planthopper (Nilaparvata lugens) attacks - AGUNG NUGRROHO PUSPITO; NOOR ROZZITA; MELLFANI RHAMADINDA NENDRA TIGARA; SATRIA ISKANDAR DINATA PUTRA; SRI HARTATIK; IKA PURNAMASARI; MOHAMMAD UBAIDILLAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Puspito AN, Tigara MRN, Putra SID, Rozzita N, Ubaidillah M. 2023. Molecular screening of local Indonesian rice to identified resistant varieties against brown planthopper (Nilaparvata lugens) attacks. Biodiversitas 24: 5503-5512. Brown planthopper (Nilaparvata lugens Stal) is a significant pest in rice (Oryza sativa L.), resulting in a yield loss of around 20-80%. Environmentally friendly control involves looking for potential resistance in local Indonesian rice, because it’s naturally resistant to pests and diseases and has several tolerant mechanisms for dealing with stress. However, the resistance potential of local rice has not been widely studied, so it is necessary to carry out screening to identify the resistance possessed by local Indonesian rice and continue with molecular analysis to validate the presence of brown planthopper resistance genes. This study aimed to determine the possible resistance level of 24 Indonesian local rice varieties to brown planthopper pests. The research was conducted at the Agrotechnology Laboratory, Faculty of Agriculture, University of Jember. In June-November 2022. This research included screening using the third instar nymph brown planthopper, preference testing to analyze the preference level for each local rice variety and molecular analysis using six BPH markers (RM 247, RM 6869, RM 19291, g12140-2, RM 3331, and RM 5479) with the MAS technique. The results showed that in the preference test, Lahoten, Fatuk Masin, and Sukamandi had a higher preference value than other local Indonesian rice. In the screening, the average local rice with very resistant criteria is Leukat Medan, while those with moderately vulnerable criteria are Sukamandi. In the molecular analysis of local Indonesian rice, the Aek Sibundong variety had the most resistance, while the Kapuas and Sukamandi varieties had the least resistance.